Development of Interactive Learning Media in Media and Telecommunication Network Subjects at Vocational High School - Veri Kurtis; Dedy Irfan (JTP - Jurnal Teknologi Pendidikan, 2024)
This research aims to develop Android-based interactive learning media that can improve student learning outcomes in MJT subjects at SMKN 4 Payakumbuh. This research uses a research and development method with a 4-D model (Define, Design, Develop, Disseminate). Data was collected through a questionnaire distributed to class X TJKT students. The research results show that the use of Android-based interactive learning media can improve student learning outcomes. From the paired sample t-test, a sig (2-Tailed) value of 0.000 <0.05 was obtained, indicating that there is a significant influence of interactive learning media on student learning outcomes. Apart from that, the practicality test shows that this interactive learning media is practical and can be well received by students and teachers. The development of interactive learning media was carried out in accordance with the MJT material taught to class X TJKT students. The validity of this interactive learning media is high, with an average validity value of 0.85. The practicality test shows that this media is practical with a percentage of 82% of teachers and 85.7% of students. The effectiveness of this media can also be seen from the percentage of completeness of student learning outcomes which reached 75.86%. This Android-based interactive learning media helps students to learn independently and improve their understanding of MJT subject matter. The development of Android-based interactive learning media is effective in improving student learning outcomes in MJT subjects at SMKN 4 Payakumbuh. This media is valid, practical, and well received by students and teachers. Thus, this interactive learning media is an effective solution to overcome low student learning outcomes and limited computer facilities in schools.